2018
DOI: 10.1002/iub.1743
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic acid phenethyl ester guards against benign prostate hypertrophy in rats: Role of IGF‐1R/protein kinase‐B (Akt)/β‐catenin signaling

Abstract: Benign prostate hypertrophy (BPH) is among the most common diseases with a huge impact on the quality of life of elderly men. There is a current need for the development of well-tolerated and effective preventive strategies to improve the clinical outcome. Caffeic acid phenethyl ester (CAPE) is an important active ingredient isolated from honey-bee propolis with potent anti-proliferative, anti-inflammatory and antioxidant effects. These properties promote CAPE as a promising candidate to be tested as an altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Oxidative stress is also considered to be one of the mechanisms that cause early pathological changes during prostate hyperplasia [ 60 ]. Oxidative stress can promote prostate hyperplasia by affecting the apoptosis pathway of prostate cells [ 61 ], inducing prostatitis [ 62 , 63 ], and accelerating prostate proliferation [ 64 ] by activating the PI3K/Akt signalling pathway. Androgen can induce oxidative stress by increasing free radicals [ 65 ] and physiological amount of estrogen has antioxidant effect, but over-physiological amount of estrogen may induce oxidative stress by causing mitochondrial dysfunction [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress is also considered to be one of the mechanisms that cause early pathological changes during prostate hyperplasia [ 60 ]. Oxidative stress can promote prostate hyperplasia by affecting the apoptosis pathway of prostate cells [ 61 ], inducing prostatitis [ 62 , 63 ], and accelerating prostate proliferation [ 64 ] by activating the PI3K/Akt signalling pathway. Androgen can induce oxidative stress by increasing free radicals [ 65 ] and physiological amount of estrogen has antioxidant effect, but over-physiological amount of estrogen may induce oxidative stress by causing mitochondrial dysfunction [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the development of BPH is dependent on steroid hormones [ 79 ]. The key genes IGF1 and EPHA7, important seed genes in the modules and hub genes in several algorithms, were also identified, and previous studies have shown that IGF1 is associated with the development of BPH [ 64 , 80 , 81 ]. Findings involving EPHA7 have not been reported in most studies of BPH, although one study found that EPHA7 expression was upregulated in BPH tissue or normal tissue compared to most PCa samples [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was known that the development of BPH was dependent on steroid hormones 55 . The key genes IGF1 and EPHA7, important seed genes in the modules and hub genes in several algorithms, were also obtained, and previous studies have shown that IGF1 is associated with the development of BPH [56][57][58] . While EPHA7 had not been reported in studies of BPH, and one study found EPHA7 expression was upregulated in BPH tissue or normal tissue compared to most PCa samples 59 .…”
Section: Discussionmentioning
confidence: 99%
“…The constituents of QLX include numerous polyphenols and polyphenolic metabolites such as caffeic acid, gallic acid, p ‐coumaric acid, protocatechuic acid, neochlorogenic acid and chlorogenic acid. Dietary polyphenols are known to benefit management of BPH and CNP 35‐37 . The evidence suggested that QLX exerts a prostatic protective function and might be used to relieve LUTS associated with CNP and BPH.…”
Section: Discussionmentioning
confidence: 99%